Factors that influence women entrepreneurial success in Malaysia: A conceptual framework - Abd Rani, Shamsul Hana; Hashim, Norashidah (2015)
This study focus on examined the factors which influence the success of women entrepreneurs in Malaysia.This study is going to focus on individual factors which consist of entrepreneurial characteristics, work experience and training. Based on previous literature, there are four characteristics which frequently cited to influence the success among women entrepreneurs which are need for achievement, risk taking, self confidence and creative and innovative.Besides, women entrepreneurs as well need work experience and training in order to develop themselves and become successful entrepreneurs.In this study, the success of women entrepreneur will be measured by non-financial aspects because women will become less successful if compared in terms of financial aspects since they usually owned small and slower growing business.Thus, this study will adapt the subjective measurement of entrepreneurial success which is work life balance satisfaction since only few studies has used it in measuring success of women entrepreneurs.